2009
DOI: 10.1002/ase.110
|View full text |Cite
|
Sign up to set email alerts
|

Near‐peer teaching in anatomy: An approach for deeper learning

Abstract: Peer teaching has been recognized as a valuable and effective approach for learning and has been incorporated into medical, dental, and healthcare courses using a variety of approaches. The success of peer teaching is thought to be related to the ability of peer tutors and tutees to communicate more effectively, thereby improving the learning environment. Near-peer teaching involves more experienced students acting as tutors who are ideally placed to pass on their knowledge and experience. The advantage of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
279
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(296 citation statements)
references
References 28 publications
13
279
0
4
Order By: Relevance
“…Therefore, to maximize reliability of knowledge while attempting to overcome the shortage of anatomy demonstrators, near-peer tutoring has been suggested as a possible solution by Evans and Cuffe (2009), which was positively received by fourth-year tutors and their first-and second-year students. More senior students teach their junior peers in hope of reinforcing and expanding their own knowledge as well as developing teaching and communication skills that they will be expected to utilize in a supervisory role throughout their careers.…”
Section: Peer-peer Partnershipsmentioning
confidence: 99%
“…Therefore, to maximize reliability of knowledge while attempting to overcome the shortage of anatomy demonstrators, near-peer tutoring has been suggested as a possible solution by Evans and Cuffe (2009), which was positively received by fourth-year tutors and their first-and second-year students. More senior students teach their junior peers in hope of reinforcing and expanding their own knowledge as well as developing teaching and communication skills that they will be expected to utilize in a supervisory role throughout their careers.…”
Section: Peer-peer Partnershipsmentioning
confidence: 99%
“…Multiple reports compare problem-based learning (Azer and Eizenberg, 2007), peer teaching (Krych et al, 2005;Evans and Cuffe, 2009), team-based learning (Nieder et al, 2005), computer or web-based teaching materials (Bryner et al, 2008;Petersson et al, 2009), and clinical skills (Dusseau et al, 2008) with traditional dissection methodology. Winkelmann (2007) reviewed several novel teaching methods and found that they were mostly judged to be ''not disadvantageous'' while at the same time not achieving significantly better results than traditional teaching methods on comparable examinations.…”
Section: Introductionmentioning
confidence: 99%
“…It is through this preparation that student teachers are deepening their own learning and becoming better overall learners [11][12]. They are better able to anticipate learning issues due to the similarity of their knowledge and relying on successful strategies they used as learners [1].…”
Section: Introductionmentioning
confidence: 99%